Narrating Cuba: The Chronicles of Manuel Serafín Pichardo at the World’s Columbian Exposition (1893) (Islas, 2023)
Introduction: This article analyzes the Cuban national narrative that emerges from the book La Ciudad Blanca, by the Cuban journalist and intellectual, Manuel Serafín Pichardo. The book constitutes a collection of chronicles that illustrates Pichardo's visit to the Chicago Columbian Exposition, which took place in 1893.Methods: The contents of the book are analyzed through Critical Discourse Analysis, situating the construction of national identity as the result of a dialogic practice between the Cuban narrator and the encounter with the US American «other».Results: Through a process of negotiation with the hegemonic postulates of the fair, by which the United States traces itself as the new imperial power, Cuban identity is constructed as essentially agricultural and independent, capable of belonging to the concert of the «civilized» world.Conclusions: The discourse of Cubanness that Pichardo exhibits in his chronicles is a result of a process of negotiation of the place that Cuba ought to occupy in modernity, reflecting practices of submission and resistance to the dominant ideologies circulating at the fair.
Keywords: Cuba; World’s Columbian Exposition; national identity; La Ciudad Blanca; discourse analysis